The Integrated Role of Individual Characteristics, Self-Efficacy, and Competence in Improving Employee Performance - Ni Kadek Ayu Novita Sari; Ni Made Dwi Puspitawati; Tiara Carina (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Employee performance refers to the work results and work behavior achieved in completing assigned tasks and responsibilities within a specific period. This study was conducted to examine the influence of individual characteristics, self-efficacy, and competence on employee performance at the Infinity Training Centre Badung. The study population consisted of all 34 employees at the Infinity Training Centre Badung, and a saturated sample was used. To achieve the desired objectives, the study employed multiple linear regression. The results indicated that individual characteristics have a positive and significant effect on employee performance at the Infinity Training Centre Badung, self-efficacy has a positive and significant effect on employee performance at the Infinity Training Centre Badung, and competence has a positive and significant effect on employee performance at the Infinity Training Centre Badung.